Effects of fan placement on smoke spread and occupant evacuation in highway tunnel fires - Liu, Zhen; Zhao, Rongxuan; Wang, Jixin (Frontiers in Built Environment, 2025)
IntroductionAs urbanization accelerates, highway tunnels are proliferating across China. Owing to their semi-enclosed geometry, the primary objectives in a tunnel fire are immediate smoke extraction and toxic-gas dilution to rescue trapped occupants. Yet current research struggles to capture long-range smoke spread in full-scale tunnels and often overlooks how the relative position between fans and the fire source affects flow patterns.MethodsTherefore, this study investigates highway-tunnel fire smoke and occupant evacuation using full-scale experiments, theoretical analysis and FDS simulations.ResultsUnder low-intensity fire conditions, the critical longitudinal wind speed ranges between 1 and 3 m/s. Ventilation velocity shows a positive correlation with smoke-layer thickness near the fire source, while back-layering length is negatively correlated with fan speed. Fan location significantly influences temperature, visibility and CO volume fraction. The closer the fan is to the fire, the lower the temperature, the higher the visibility and the smaller the CO volume fraction, all of which favor evacuation. At constant walking speed, shortening the fan-to-fire distance reduces both the required and available safe egress times, thereby accelerating evacuation.DiscussionBy linking back-layering length, temperature, visibility and CO volume fraction to evacuation time, this work provides both theoretical foundations and real-time data for tunnel emergency response, enabling rapid intervention and safeguarding lives and property.